XIX-wieczne procesy tworzenia Japońskiego Kodeksu Cywilnego - Jelonek, Barbara (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2014)
The nineteenth-century reforms associated with creating the Japanese Civil Code are an example of the fruits of comparative jurisprudence. The codification of private law in Japan was the result of a great political and social revolution, which in turn was the consequence of the country’s opening up to and accepting of Western ideas. The influence of Western sources on Japanese law is visible not only in civil law but also criminal and commercial law, and furthermore in the change of attitudes in traditional Japanese thinking, which had previously been derived exclusively from Chinese sources. This article is a response to the absence of the aforementioned subject from research papers concerning the history of the Japanese state and law. In the author’s view, this matter is key, inter alia, for economic and political reasons. Therefore, it requires a thorough analysis, while the abovementioned issues should be included in the literature on the history of state and law.
Keywords: japoński kodeks cywilny; westernizacja; komparatystyka prawnicza; Hozumi, Nobushige (1855-1926)